Strategi Guru Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Di Kelas 3A MI Terpadu Muatiara Assyifa Kota Bengkulu - Rosefi, Tiara Septa; Wulandari, Friesca; Virginia, Serly; Sari, Mike Puspita; Asvio, Nova (JPT : Jurnal Pendidikan Tematik, 2023)
Improving learning outcomes can be done by improving the learning process. This study aims to determine the learning strategies used by class 3A teachers in conducting learning in formal education. This study uses descriptive qualitative. The type of research conducted is the data collection method applied includes observation and interviews. The results of this study are learning strategies are very important, in fact, the strategy is one of the first that must be considered and prepared so that learning can run effectively and efficiently as well as more interesting. To overcome some of the inhibiting factors that teachers find in the classroom, there are several things that teachers do to overcome them. In implementing learning strategies, teachers often encounter obstacles such as a lack of facilities and infrastructure. The solution to avoid this is by providing other options such as creating their own learning media, changing learning strategies that can be understood by students. Teachers always adjust the strategies used with existing facilities and continue to innovate despite the limitations of these facilities. The point is never to make an obstacle to not doing something new.